ANALISIS PENGARUH KUALITAS PELAYANAN ONLINE FOOD DELIVERY PADA APLIKASI GOJEK TERHADAP KEPUASAN KONSUMEN (Studi Pada Mahasiswa Universitas Bhayangkara Jakarta Raya) - Annisa Rachma Tsaniyah; Aprilia Prahanita, Dita Listiyana, Nesya Rahmawati, Tria Fajriana, Dian Sudiantini (CV. Adiba Aisha Amira, 2024)
The purpose of this study to analyze the eflect of online food delivery service quality in the Gojek application on customer satisfaction, this research was conducted at the Faculty of Economics and Business, Bhayangkara Jakarta Raya University. The random sampling technique was used to determine the sample in this study, where the respondents were students. The number of samples used was 50 people. The results of this study provide recommendations for improvements to Gojek based on an analysis of the eflect of service quality on customer satisfaction. The findings show that ease of use of the application, accuracy of order delivery, and transparency in communication regarding delays are important factors that aflect customer satisfaction. In addition, trust in GoFood services is also a key factor in maintaining customer satisfaction.